Konsumsi Kopi Berhubungan Dengan Sindrom Mata Kering - Fayola, Aurelia Putri; Kartadinata, Erlani (Jurnal Biomedika dan Kesehatan, 2023)
Background Dry eye syndrome is an eye disorder that affect tear film and can causes damage to the surface of the eyes. This disease is one of the health burdens because of its high prevalence. There are various risk factors for dry eye syndrome, one of which is coffee consumption, due to its high caffeine content. The purpose of this study was to assess the association between coffee consumption and dry eye syndrome in adults. Methods An analytic observational study with a cross-sectional design was used for this research. The population in this study were adults (20 – 59 years old) in RW 07 Panaragan Pojok with sample size of 115 people who were taken using cluster random sampling and simple random sampling. Data were collected through filling out questionnaires regarding coffee consumption and filling out OSDI questionnaires. Research data was analyzed using the Chi-square test. Results The results of this study shows that subjects who have dry eye syndrome are dominated by late adults in age 30 – 9 years old and male sex. Of all subjects with dry eye syndrome, most of them have a habit of consuming coffee, especially in light consumption. There is no relationship between gender (p = 0,776) and age (p = 0,221) with dry eye syndrome. Meanwhile, it was found that there is a relationship between coffee consumption and dry eye syndrome (p = 0,000). Conclusions This study shows that coffee consumption is associated with dry eye syndrome in adulthood. However, it was found that there is no significant relationship between sociodemographic characteristics (age and gender) and dry eye syndrome.